Social networking sites: the awareness among youngsters in Malaysia / Heather Marie Anthony … [et al.] - Anthony, Heather Marie; Mohd Razali, Mohamad Azmir; Md Nor Azman, Nurul Aliaa; Redwan, Rais Shahmi (2009)
Despite the popularity of the social networking sites (SNSs) nowadays, this research project is primarily aimed for youngsters who are actively engaged in social networking sites (SNSs) as a subject to create awareness among them on the safety of the social networking sites (SNSs). It is a compilation of books, journals and articles from the Internet, and questionnaires distributed to students from selected schools around Kuala Lumpur and Selangor. Apart from that, the case of Lori Drew is the yardstick in looking into the seriousness of social networking sites (SNSs) in real life to the youngsters. This research project has taken note of social networking sites (SNSs) and its popularity among students and to examine whether youngsters aware of the negative effects of social networking sites (SNSs) and how to make it safe for them. In addition, this research project gave the ideas on the measures that should be taken not only by the social networking providers but public as a whole to protect the youngsters from any dangers created from social networking sites (SNSs). It is hoped that this research project will be a valuable aid for the youngsters to acquaint themselves with the possible consequences of social networking sites (SNSs), and provide some solutions to it, and create a safer virtual environment for them.